Chemistry Design Towards a Stable Sulfide‐Based Superionic Conductor Li4Cu8Ge3S12. (29th April 2019) - Wang, Yingqi; Lü, Xujie; Zheng, Chong; Liu, Xiang; Chen, Zonghai; Yang, Wenge; Lin, Jianhua; Huang, Fuqiang
Abstract: Sulfide‐based superionic conductors with high ionic conductivity have been explored as candidates for solid‐state Li batteries. However, moisture hypersensitivity has made their manufacture complicated and costly and also impeded applications in batteries. Now, a sulfide‐based superionic conductor Li4 Cu8 Ge3 S12 with superior stability was developed based on the hard/soft acid–base theory. The compound is stable in both moist air and aqueous LiOH aqueous solution. The electrochemical stability window was up to 1.5 V. An ionic conductivity of 0.9×10 −4  S cm with low activation energy of 0.33 eV was achieved without any optimization. The material features a rigid Cu‐Ge‐S open framework that increases its stability. Meanwhile, the weak bonding between Li + and the framework promotes ionic conductivity. This work provides a structural configuration in which weak Li bonding in the rigid framework promotes an environment for highly conductive and stable solid‐state electrolytes. Abstract : Ein hart‐weicher Leiter : Auf Grundlage der Theorie der harten und weichen Säuren und Basen wurde ein Sulfid‐basierter superionischer Leiter entwickelt. Das Li4 Cu8 Ge3 S12 ‐Material hat eine einzigartige Strukturkonfiguration, bei der die Kombination aus schwach gebundenem Li in einem starren Gerüst sowohl hohe Leitfähigkeit als auch herausragende Stabilität verleiht.